Effects of innovation on employment: a dynamic panel analysis - Stefan Lachenmaier; Horst Rottmann (Center for Economic Studies and ifo Institute (CESifo), 2007)
This paper estimates the effect of innovation on employment at the firm level. Our uniquely long innovation panel data set of German manufacturing firms covers more than 20 years and allows us to use various innovation measures. We can distinguish between product and process innovations as well as between innovation inputs and innovation outputs. Using dynamic panel GMM system estimation we find positive effects of innovation on employment. This result is robust to the use of product and process innovations as well as for innovation input and output.
Keywords: O30; L60; C23; J23; 330; Innovation; Verarbeitendes Gewerbe; Industrielle Beschäftigung; Beschäftigungseffekt; Schätzung; Deutschland